Clinical study of azithromycin - Matsumoto, Fumio; Imai, Takeo (Japanese Journal of Chemotherapy, 1995)
The clinical effect of azithromycin (AZM), a newly developed azalide antibacterial agent, was examined, with the following results. The subjects were 7 patients, including 2 cases of acute bronchitis, 4 of chronic bronchitis and 1 of pneumonia. The result was evaluated as good in all 7 cases. As for the bacteriological effect, Haemophilus influenzae isolated from 1 case of chronic bronchitis was eradicated by AZM. No adverse reactions or abnormal changes in laboratory values were observed throughout the study period